Seeing the forest as more than its trees: local stakeholders’ perceptions of natural forest benefits in Gorontalo, Indonesia - Kartikasari, S.N.; Rixecker, S.; Espiner, S.R.; Colfer, C.J.P. (2009)
Gorontalo’s tropical forest is of global importance and is the last stronghold for conserving Sulawesi’s unique biodiversity. However, implementation of biodiversity conservation at the local level has been fraught with very complex, rooted in increased pressures on natural resources and its ecological services to meet the socioeconomic development goals. One problem in implementing forest conservation lies in defining the benefits local people receive from it and who enjoys these benefits. This paper explores local perceptions of forest biodiversity conservation. Understanding local perceptions is necessary for successful implementation of conservation activities. Interviews and a ranking exercise were conducted in the Gorontalo Province, Sulawesi and Indonesia. Data were collected in 2005, involving 152 participants from 6 distinct stakeholder groups, from both government and non-government organisations. The results presented here is based on the analysis of findings from the ranking exercise. Local stakeholders valued the natural forest most highly for its ecological services.